2018
DOI: 10.3389/fphar.2018.00542
|View full text |Cite
|
Sign up to set email alerts
|

Association Between ABCB1 Polymorphism and Stable Warfarin Dose Requirements in Brazilian Patients

Abstract: The ideal dose of the oral anticoagulant warfarin varies widely among patients, mainly due to genetic factors. Genetic variations that impact warfarin pharmacokinetics and the vitamin K cycle are plausible candidates for being associated with warfarin dose requirements. Therefore, the aim of this study was to assess whether polymorphisms in the ABCB1 and CYP4F2 genes were associated with stable warfarin dose requirements in Brazilian patients. This retrospective study included samples from 309 individuals. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
0
16
0
5
Order By: Relevance
“…Se encontraron 402 artículos científicos referidos a la farmacogenética de la warfarina, de estos 382 fueron excluidos por no incluir población latinoamericana. Se identificaron 20 artículos realizados en población latinoamericana, de estos, sólo once cumplieron con los criterios de inclusión, los restantes nueve artículos (Tavares, 2018;Valentín, 2014;Guerrero, 2009;Isaza, 2010;Raggio, 2005; Claudio-Campos, 2015; Parra, 2015; Villagra, 2010) fueron excluidos (Fig. 1).…”
Section: Selección De Los Estudiosunclassified
See 1 more Smart Citation
“…Se encontraron 402 artículos científicos referidos a la farmacogenética de la warfarina, de estos 382 fueron excluidos por no incluir población latinoamericana. Se identificaron 20 artículos realizados en población latinoamericana, de estos, sólo once cumplieron con los criterios de inclusión, los restantes nueve artículos (Tavares, 2018;Valentín, 2014;Guerrero, 2009;Isaza, 2010;Raggio, 2005; Claudio-Campos, 2015; Parra, 2015; Villagra, 2010) fueron excluidos (Fig. 1).…”
Section: Selección De Los Estudiosunclassified
“…Muchos factores clínicos y ambientales como la edad, sexo, raza, índice de masa corporal, comorbilidades (principalmente enfermedades renales o hepáticas), polimedicación (Zhang,2016), consumo de tabaco, dieta, metabolismo rápido de vitamina K, así como mutaciones genéticas afectan los requerimientos de dosis de warfarina (Bryk, 2018). Los polimorfismos genéticos en los genes de la subunidad 2C9 del complejo de citocromo P450 (CYP2C9) y la subunidad 1 del complejo de la vitamina K epóxido reductasa (VKORC1) se han asociado en un 40 % a 60 % con la variación en la respuesta interindividual a la warfarina (Flockhart, 2008;Dean, 2012;Tavares, 2018;Razavi, 2017;Wattanachai, 2017;.…”
Section: Introductionunclassified
“…A considerably poorer performance was described for another PGx algorithm based on VKORC1 and CYP2C9 polymorphisms . In separate publications, the same group concluded that “genetic information on CYP2C9 and VKORC1 is important both for the initial dose‐finding phase and during maintenance treatment with warfarin”, “amiodarone influences warfarin maintenance dose” while not being associated with adverse events and CYP4F2 rs2108622 has no effect of warfarin dose requirements in their patients, whereas the ABCB1 c.3435T allele marginally affected the dose requirements . The direction of the latter effect was opposite to previously reported higher warfarin dose requirement in thrombophilic patients with the ABCB1 c.3435T allele .…”
Section: Resultsmentioning
confidence: 94%
“…Whether P-glycoprotein acts on warfarin transport remains controversial. Studies have suggested that the C3435T polymorphism in the MDR1 gene does not affect the steady-state concentration of warfarin alone [13], whereas Tavares et al [14] reported different conclusions. Our data suggested that differences in the MDR1 genotype did not significantly affect warfarin plasma concentrations.…”
Section: Discussionmentioning
confidence: 99%